2015
DOI: 10.4278/ajhp.140618-quan-287
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tai Chi on Cardiovascular Risk in Women

Abstract: Purpose This study examined the effects of tai chi (TC) on biobehavioral factors associated with cardiovascular disease (CVD) risk in women. Design A randomized trial used a wait-list control group, pretest-posttest design. Data were collected immediately before, immediately after, and 2 months following the intervention. Setting The study was community based in central Virginia. Subjects Women aged 35 to 50 years at increased risk for CVD. Intervention The 8-week intervention built on prior work and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 42 publications
1
27
0
1
Order By: Relevance
“…[1][2][3][4][5][6][8][9][10][11] Among these 9 studies, 3 were conducted in middle-aged or older cancer survivors, 3,4,6,9 4 studies were conducted in other subgroups of older adults (healthy older adults, and older adults with insomnia, depression, or mild cognitive impairment), 2,5,8,11 1 study was conducted in HIV-infected adults, 1 and 1 study was conducted in women with elevated cardiovascular disease risk. 10 All studies, except for 1, 10 included an active control group that received health education, cognitive behavioral therapy, or other interventions. The terms ranged from 3 weeks to 6 months, and the doses varied as the duration ranged from 1 to 2 h and the frequency ranged from one time per week to three times per week.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][8][9][10][11] Among these 9 studies, 3 were conducted in middle-aged or older cancer survivors, 3,4,6,9 4 studies were conducted in other subgroups of older adults (healthy older adults, and older adults with insomnia, depression, or mild cognitive impairment), 2,5,8,11 1 study was conducted in HIV-infected adults, 1 and 1 study was conducted in women with elevated cardiovascular disease risk. 10 All studies, except for 1, 10 included an active control group that received health education, cognitive behavioral therapy, or other interventions. The terms ranged from 3 weeks to 6 months, and the doses varied as the duration ranged from 1 to 2 h and the frequency ranged from one time per week to three times per week.…”
Section: Resultsmentioning
confidence: 99%
“…Among 26 articles, 13 articles met the inclusion criteria. [1][2][3][4][5][6][7][8][9][10][11][12][13] There were two sets of articles that describe the same studies. 3,4,7,8 The authors combined the two articles for one study, 3,4 and included one article for the other study.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed information on the design and methods of four of the studies can be found in the original reports (Ameringer et al, 2014; Jallo, Ruiz, Elswick, & French, 2014; Menzies et al, 2014; Robins et al, 2015). One study examined fatigue in fibromyalgia (FMS) (Menzies et al, 2014), another in sickle cell disease (SCD) (Ameringer et al, 2014), a third in cardiometabolic risk (CMR) (Robins et al, 2015), and a fourth in pregnancy (Jallo et al, 2014). In the fifth study, fatigue was examined in healthy controls and women with breast cancer; here, data from the healthy control subsample were used to examine known groups validity only.…”
Section: Methodsmentioning
confidence: 99%
“…In cardio-metabolic risk and cardiac disease, the pathophysiology may be attributable to alterations of insulin action, such as insulin resistance and the low-grade inflammatory state, due in part to cytokines produced by the excessive adipose tissue (Kaltsas, Vgontzas, & Chrousos, 2010). It is postulated that perceived stress and depressive symptoms contribute to fatigue and weight gain, which increases cardio-metabolic risk and, ultimately, cardiovascular disease (Robins, Elswick, Sturgill, & McCain, 2015). During pregnancy, the pathogenesis of fatigue is likely related to physiologic changes such as increased oxygen consumption, cardiovascular changes, metabolic effects, as well hormones such as progesterone (Poole, 1986).…”
mentioning
confidence: 99%
“…Algunos estudios han sugerido que su práctica mejora los niveles de ansiedad (13) , presión arterial y riesgo cardiovascular (14) así como el dolor/ discapacidad en enfermedades músculo-esqueléticas como la osteoartritis (15,16) . Así, el objetivo de este estudio es evaluar los grados de estrés en adultos mayores de 60 años que practican regularmente taichí en comparación a quienes no lo realizan, en un establecimiento de salud de la ciudad de Trujillo, durante el año 2014.…”
Section: Introductionunclassified